2003
DOI: 10.1016/s1097-2765(03)00038-8
|View full text |Cite
|
Sign up to set email alerts
|

The Human Sir2 Ortholog, SIRT2, Is an NAD+-Dependent Tubulin Deacetylase

Abstract: The silent information regulator 2 protein (Sir2p) of Saccharomyces cerevisiae is an NAD-dependent histone deacetylase that plays a critical role in transcriptional silencing. Here, we report that a human ortholog of Sir2p, sirtuin type 2 (SIRT2), is a predominantly cytoplasmic protein that colocalizes with microtubules. SIRT2 deacetylates lysine-40 of alpha-tubulin both in vitro and in vivo. Knockdown of SIRT2 via siRNA results in tubulin hyperacetylation. SIRT2 colocalizes and interacts in vivo with HDAC6, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
1,360
4
14

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 1,406 publications
(1,424 citation statements)
references
References 26 publications
46
1,360
4
14
Order By: Relevance
“…The dependency of class III enzymes on NAD þ could also link the activity of the complex to the metabolic status of the cell. A similar combination of class II and class III enzymes in a multiprotein complex was recently observed for HDAC6 and SIRT2, a human class III HDAC [56]. SMRTand N-CoR interact both with class IIa HDACs and with HDAC3 through distinct domains [52,53,57,58], an observation that explains why class IIa HDACs coimmunoprecipitate with HDAC3 [5,16,48].…”
Section: Dynamic Subcellular Localizationsupporting
confidence: 67%
See 2 more Smart Citations
“…The dependency of class III enzymes on NAD þ could also link the activity of the complex to the metabolic status of the cell. A similar combination of class II and class III enzymes in a multiprotein complex was recently observed for HDAC6 and SIRT2, a human class III HDAC [56]. SMRTand N-CoR interact both with class IIa HDACs and with HDAC3 through distinct domains [52,53,57,58], an observation that explains why class IIa HDACs coimmunoprecipitate with HDAC3 [5,16,48].…”
Section: Dynamic Subcellular Localizationsupporting
confidence: 67%
“…HDAC6 overexpression promotes chemotactic cell movement, a cellular function dependent on microtubules. We have independently observed that SIRT2, a NAD þ -dependent class III HDAC, deacetylates lysine 40 of a-tubulin both in vitro and in vivo [56]. Both HDAC6 and SIRT2 interact and co-localize in the cytoplasm with the microtubule network (Fig.…”
Section: Tigs 54mentioning
confidence: 92%
See 1 more Smart Citation
“…2003), we previously showed the enrichment of Sirt2 protein on the meiotic apparatus—the spindle and midbody during oocyte maturation (Zhang et al., 2014). In support of this observation, we here confirmed that Sirt2 knockdown in mouse oocytes results in spindle defects and chromosome disorganization, with impaired K‐MT attachment.…”
Section: Discussionmentioning
confidence: 95%
“…For example, histone H4K16 and α‐tubulin‐K40 have been indicated as the potential targets of Sirt2 to modulate chromatin conformation and microtubule stability (North et al., 2003; Vaquero et al., 2006). Sirt2 participates in myelin formation of Schwann cells by deacetylating partitioning defective 3 homologue (PAR3) (Beirowski et al., 2011).…”
Section: Discussionmentioning
confidence: 99%